The Wage Bargaining Structure in Norway and Sweden and its Influenceon Real Wage Developments - Thomas, Alun (IMF Working Papers; Working Paper ;, 1998)
The paper investigates the determinants of wages in the tradables and service sectors in Norway and Sweden. Tradables wages are determined by their own productivity growth whereas service sector wages are influenced by wage growth in the tradables sector. The traditional strong sensitivity of the real wage to changes in the unemployment rate has been virtually eliminated since the recessionary period in the early 1990s in Sweden, and real wages have grown faster than macroeconomic factors alone would suggest. In contrast, real wages have become more sensitive to cyclical conditions in Norway and have grown less rapidly than macroeconomic factors indicate. These changes in the wage process have hindered the development of private sector employment in Sweden but have stimulated private sector employment in Norway.